Meningkatkan Aktivitas, Keterampilan Sosial, Dan Hasil Belajar Siswa Mata Pelajaran Ppkn Menggunakan Model “BAGUS” Pada Siswa Kelas IV SDN MAWAR 8 Banjarmasin - Prasetiya, Randra; Hidayat, Ari (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The problem in this research is the low level of student activity, social skills, and learning outcomes. This is due to students tending to be passive, the suboptimal use of varied teaching models, and low social awareness among students. The effort to address these issues is by implementing the BAGUS learning model, which is a combination of Problem Based Learning, Number Head Together, and Sociodrama. The aim of this research is to describe teacher activities, analyze student activities, analyze students' social skills, and improve student learning outcomes. This research uses Classroom Action Research (CAR) conducted over four meetings. The subjects of this study are 15 fourth-grade students from SDN Mawar 8, Banjarmasin, consisting of 7 boys and 8 girls, during the first semester of the 2023/2024 academic year. The results of this study show an improvement in each meeting in teacher activities, with a score of 14 in the first meeting increasing to 38 in the fourth meeting. Then, in student activities, the first meeting showed a percentage of 33%, which increased to 93% by the fourth meeting. As for social skills, the first meeting showed a percentage of 27%, which increased to 93% by the fourth meeting. For cognitive learning outcomes, classical completeness increased from 33% to 100% from the first to the fourth meeting. The effective learning outcomes classical completeness increased from 27% to 93% from the first to the fourth meeting. Lastly, the psychomotor learning outcomes classical completeness increased from 33% to 93% from the first to the fourth meeting. Based on these research results, it can be concluded that the use of the BAGUS model can improve the quality of teacher activities, student activities, social skills, and student learning outcomes. Recommendations for school principals, teachers, students, and other researchers are to use this research as a reference in employing learning models that can enhance the quality of teacher activities, student activities, social skills, and student learning outcomes.